Persuasive technology : 13th international conference, PERSUASIVE 2018, Waterloo, ON, Canada, April 18--19, 2018 proceedings /: 13th international conference, PERSUASIVE 2018, Waterloo, ON, Canada, April 18--19, 2018 proceedings. (2018) - Unknown
No abstract available